2009
DOI: 10.1186/ar2601
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow lesions from osteoarthritis knees are characterized by sclerotic bone that is less well mineralized

Abstract: Introduction Although the presence of bone marrow lesions (BMLs) on magnetic resonance images is strongly associated with osteoarthritis progression and pain, the underlying pathology is not well established. The aim of the present study was to evaluate the architecture of subchondral bone in regions with and without BMLs from the same individual using bone histomorphometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
145
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(164 citation statements)
references
References 35 publications
(46 reference statements)
6
145
0
6
Order By: Relevance
“…In the current study, we carefully excised BML and non‐BML areas of a femoral head, as segregated using MRI, and were able to detect subtle differences in MSC features within the same affected joint but in relation to the amount of tissue damage. The histologic features of excised BML and non‐BML regions in our study were consistent with anticipated tissue abnormalities in BMLs, such as an increased bone volume fraction 24 and overlying cartilage loss 25, 26.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the current study, we carefully excised BML and non‐BML areas of a femoral head, as segregated using MRI, and were able to detect subtle differences in MSC features within the same affected joint but in relation to the amount of tissue damage. The histologic features of excised BML and non‐BML regions in our study were consistent with anticipated tissue abnormalities in BMLs, such as an increased bone volume fraction 24 and overlying cartilage loss 25, 26.…”
Section: Discussionsupporting
confidence: 81%
“…BMLs have been characterized by a high bone volume fraction 24. For trabecular area analysis, 320 images of bone were acquired: 198 images for BML samples (average of 9.3 images per sample [range 5–14]) and 122 images for non‐BML samples (average of 6.6 images per sample [range 5–9]).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, mutations of ECM proteins that bind to latent TGF-βs, such as small leucine-rich proteoglycans (87) and fibrillin (88), or mutations in genes involved in activation of TGF-β, such as in CED (76) and LDS (89), are associated with high osteoarthritis incidence. Osteoblast differentiation of MSCs in aberrant locations appears histologically as subchondral bone osteoid islets and alters the thickness of the subchondral plate and calcified cartilage zone, changes known to be associated with osteoarthritis (90,91). A computer-simulated model found that a minor increase in the size of the subchondral bone (1%-2%) causes significant changes in the mechanical load properties on articular cartilage, which likely leads to degeneration (86).…”
Section: Figurementioning
confidence: 99%
“…A number of studies point to possible causal factors for BML, including mechanical loading (Bennell et al, 2010), dietary fatty acid intake ) and total serum cholesterol and triglycerides , disturbances in the latter having well established vascular implications. BML have been described as containing bone that is sclerotic, but which has reduced mineral density, perhaps rendering the area mechanically compromised (Hunter et al, 2009). Consistent with this, is the finding that BMLs are strongly associated with subchondral bone attrition .…”
Section: Impaired Venous Blood Flow and Increased Intraosseous Pressumentioning
confidence: 74%